Alveolar Bone Dimensions in Orthodontic Unilateral Impacted Canine Cases using Cone Beam Computed Tomography: Orthodontic Unilateral Impacted Canine Cases using CBCT - Muneeb, Eesha; Raza, Anum; Rabbani, Muhammad Hadeer; Azeem, Muhammad; Ateeq, Lailah; Younis, Faryal (Pakistan Journal of Health Sciences, 2025)
Impacted canines are due to missing laterals, crowding, or genetics. The alveolar bone that acts as a shock absorber distributes the masticatory forces to the underlying tissues. Objectives: To study the mean alveolar bone dimensions on the impaction and non-impaction side of Orthodontic unilateral impacted canine cases using CBCT. Methods: This descriptive cross-sectional research was organized at the Department of Orthodontics, CMH Lahore Medical College, where 165 patients were enrolled as per the selection criteria. Bucco-palatal width of the alveolar bone was measured at the level of the alveolar crest, while alveolar bone height was calculated from the alveolar crest to the nasal floor, on the impacted side. These were compared with corresponding alveolar bone dimensions on the non-impaction side, and the values were recorded. An independent samples t-test was used to find out whether any significant difference was present, and post-stratification. A p-value<0.05 was considered significant. Results: The mean age of the patients was 34.99 ± 14.69 years. There were 77 (46.7%) male and 88 (53.3%) female. On the impacted side, the mean width of alveolar bone was 6.58 ± 0.67 mm, and the mean height was 17.28 ± 0.67 mm. On the non-impacted side, the mean width and height of alveolar bone were 8.40 ± 0.96 mm and 19.01 ± 0.96 mm, respectively (p=0.001). Conclusions: The mean width and height of the alveolar bone on the impacted canine side were lower than the respective alveolar bone dimensions on the non-impacted side.